PENGARUH PANDANGAN IKLAN DAN DAYA TARIK IKLAN TERHADAP MINAT BELI KONSUMEN DENGAN KREDIBILITAS IKLAN SEBAGAI VARIABEL MEDIASI - Winarsih, Endang; Martani, Yeni; Ngaisah, Ngaisah (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study was to determine the effect of Ad Views, Ad Attractiveness with Ad Credibility as a Mediating Variable at the Lowo Sukoharjo Building Culinary Festival. The method used in this research is quantitative method with PLS. The results showed partially that the advertising view variable has a significant effect on advertising credibility with, advertising attractiveness has a significant effect on advertising credibility, advertising views have a significant effect on buying interest, advertising attractiveness has a significant effect on buying interest. Simultaneously, advertising views and advertising attractiveness have a positive and significant effect on consumer buying interest in the Lowo Sukoharjo Building Culinary Festival. Based on the research results, suggestions for managers to use other advertising stars from various groups such as entrepreneurs, sportsmen or public figures to attract visitors. Keywords: View Advertising , Ad Attractiveness , Consumer Purchase Interest, Ad Credibility